Assessing the Role of Microfinance in Fostering Adaptation to Climate Change - Agrawala, Shardul (OECD Publishing, 2010)
Much of the current policy debate on adaptation to climate change has focussed on estimation of adaptation costs, ways to raise and to scale-up funding for adaptation, and the design of the international institutional architecture for adaptation financing. There is however little or no emphasis so far on actual delivery mechanisms to channel these resources at the sub-national level, particularly to target the poor who are also often the most vulnerable to the impacts of climate change. It is in this context that microfinance merits a closer look. This paper offers the first empirical assessment of the linkages between microfinance supported activities and adaptation to climate change. Specifically, the lending portfolios of the 22 leading microfinance institutions in two climate vulnerable countries - Bangladesh and Nepal - are analysed to assess the synergies and potential conflicts between microfinance and adaptation. The two countries had also been previously examined as part of an earlier OECD report on the links between macro-level Official Development Assistance and adaptation. This analysis provides a complementary "bottom-up" perspective on financing for adaptation. Insights from this analysis also have implications for OECD countries. This is because microfinance is also being increasingly tapped to reduce the vulnerability of the poor in domestic OECD contexts as well and may therefore have the potential to contribute to adaptation. The paper identifies areas of opportunity where microfinance could be harnessed to play a greater role in fostering adaptation, as well as its limitations in this context. It also explores the linkage between the top-down macro-financing for adaptation through international financial mechanisms and the bottom-up activities that can be implemented through microfinance
Keywords: Environment